OVERVIEW OF METACOGNITIVE SKILLS ON NURSING STUDENTS - Hikmat, Rohman; Yosep, Iyus; Masala, Clausewitz Welmatus; Nahdriah, Nina (Journal of Nursing Culture and Technology, 2024)
Background: Metacognitive skills play an important role in the academic success of Nursing students. However, understanding of the description of cognitive skills in nursing students is still limited, especially at Padjadjaran University. Efforts to evaluate and understand students' cognitive skill levels can provide valuable insights for the development of more effective Nursing education curricula. Objective: This study aims to describe the cognitive skills of Padjadjaran University Nursing students. Method: This research uses quantitative descriptive. The questionnaire used is the 18 item Self-Regulated Online Learning Questionnaire (SOL-Q) to measure students' cognitive skills. The sample technique uses accidental sampling. The sample in this study was 103 nursing students at Padjadjaran University. Data analysis uses univariate analysis. Results: The results of this study showed that 103 Nursing students at Padjadjaran University were research subjects. There were 61.3% of the total research subjects who had low metacognitive skills. These findings indicate the need for special attention to the development of cognitive skills, especially metacognitive skills, in the Nursing education curriculum. Potential factors influencing students' cognitive skills also need to be further explored. Conclusion: Understanding the description of cognitive skills in nursing students can be the basis for developing more effective and targeted learning strategies.